2021
DOI: 10.3389/fnsys.2021.752320
|View full text |Cite
|
Sign up to set email alerts
|

Human Primary Olfactory Amygdala Subregions Form Distinct Functional Networks, Suggesting Distinct Olfactory Functions

Abstract: Three subregions of the amygdala receive monosynaptic projections from the olfactory bulb, making them part of the primary olfactory cortex. These primary olfactory areas are located at the anterior-medial aspect of the amygdala and include the medial amygdala (MeA), cortical amygdala (CoA), and the periamygdaloid complex (PAC). The vast majority of research on the amygdala has focused on the larger basolateral and basomedial subregions, which are known to be involved in implicit learning, threat responses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 211 publications
(248 reference statements)
0
20
0
Order By: Relevance
“…Cortical amygdala together with medial and central nuclei are often grouped together as the cortico‐medial region (LeDoux, 2007). Cortical amygdala is thought to play a role in olfactory‐related reward processing, including learning and memory of approach/avoid responses (Noto et al, 2021). It is less known how it is involved in emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical amygdala together with medial and central nuclei are often grouped together as the cortico‐medial region (LeDoux, 2007). Cortical amygdala is thought to play a role in olfactory‐related reward processing, including learning and memory of approach/avoid responses (Noto et al, 2021). It is less known how it is involved in emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…In other mammals, different sensory organs are hosted in the nasal cavity, including vomeronasal, septal organ, and Grueneberg ganglion, all projecting to the (main or accessory) olfactory bulbs ( Weiler and Farbman, 2003 ; Matsuo et al, 2012 ; Mucignat-Caretta, 2021 ), while in humans, olfactory fibers originate almost exclusively from main olfactory mucosa and run through the first cranial nerve, the olfactory nerve, and contact olfactory bulb mitral cells, the main collector of afferents. From here, olfactory projections radiate mainly, yet not exclusively, to three amygdala subregions, possibly involved in the setup of motor response to olfactory stimuli (medial amygdala), reward and memory processes (cortical amygdala), and multisensory integration (periamygdaloid complex; Noto et al, 2021 ). Notably, amygdala expresses the acid-sensing ion channel ASIC1a, which centrally senses hypercapnia and acidosis and drives the subsequent fear responses in mice ( Ziemann et al, 2009 ), while the human hortolog ACCN2 is associated with amygdala structure and function in panic disorders ( Smoller et al, 2014 ).…”
Section: Chemosensory Central Connectionsmentioning
confidence: 80%
“…The relevance of genetic background to brain microstructure was further probed by examining which ROIs had multiple dMRI measures with significant effects of strain. Excitingly, it was found that 10 ROIs had five or more dMRI measures with significant strain effects, and each of these 10 ROIs (cortical amygdalar area, lateral septal complex, dorsal hippocampal commissure, ventral hippocampal commissure, periventricular zone, lateral amygdalar nucleus, stria medullaris, fimbria, medial pallidum, and behavioral state-related pons) have previously been related to memory and AD ( Amorapanth et al, 2000 ; Maren and Quirk, 2004 ; Castaño et al, 2013 ; Badea et al, 2016 ; Butler et al, 2018 ; Colon-Perez et al, 2019 ; Kim et al, 2019 ; Postans et al, 2020 ; Beardmore et al, 2021 ; Falangola et al, 2021 ; Liao et al, 2021 ; Noto et al, 2021 ; Jordan et al, 2022 ; Juárez-Leal et al, 2022 ; Tsui et al, 2022 ), again suggesting a relationship between brain microstructure and AD outcomes.…”
Section: Discussionmentioning
confidence: 99%